2019
DOI: 10.1371/journal.pone.0217936
|View full text |Cite
|
Sign up to set email alerts
|

Functioning in schizophrenia from the perspective of psychologists: A worldwide study

Abstract: Schizophrenia is a severe mental disorder associated with impairment in functioning. A multidisciplinary approach is essential to help individuals with this health condition, and psychological interventions are considered a priority. The International Classification of Functioning, Disability and Health (ICF) offers a theoretical framework for assessing functioning and disability. The ICF Core Sets for schizophrenia are a list of ICF categories describing the most common problems in functioning of persons affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This is because previous research on the content validity of the ICF-CS with different professionals (nurses, occupational therapists, physiotherapists, psychiatrists, psychologists, and social workers) has shown that the difference in perspective between health professionals means that some ICF-CS categories for schizophrenia may be more relevant than others for a given health professional, although the way of assessing functionality is the same. [ 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because previous research on the content validity of the ICF-CS with different professionals (nurses, occupational therapists, physiotherapists, psychiatrists, psychologists, and social workers) has shown that the difference in perspective between health professionals means that some ICF-CS categories for schizophrenia may be more relevant than others for a given health professional, although the way of assessing functionality is the same. [ 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The six Delphi studies were conducted between 2016 and 2018. All studies followed the same design to ensure a high level of comparability between the results of each, and it has been detailed in the previous studies which describe the results obtained from each perspective: psychiatry [27], psychology [28], nursing [29], occupational therapy [30], social work [31] and physiotherapy [32]. Anonymity was guaranteed as the process was coordinated by a research team using an online platform or email, thus avoiding any interaction between the participants.…”
Section: Methodsmentioning
confidence: 99%
“…Schizophrenia afflicts approximately 24 million people worldwide and is a debilitating disorder for both individuals with this condition and for their families, due to its chronic course and early onset age (Patel et al, 2014;World Health Organization, 2022). Disabilities are frequently associated with schizophrenia, as its symptoms may cause hindrance in social, educational, occupational, and other important areas of life (Nuño et al, 2019). Schizophrenia is a serious illness and an important point of focus in the field of mental health.…”
Section: Schizophreniamentioning
confidence: 99%